2022
DOI: 10.1002/job.2659
|View full text |Cite
|
Sign up to set email alerts
|

Circadian leadership: A review and integration of chronobiology and leadership

Abstract: A vast body of knowledge within the field of chronobiology highlights a broad array of important effects that circadian rhythms and chronotypes have on individual performance. Circadian rhythms are predictable fluctuations of energetic activation produced by an internal pacemaker, the circadian clock, that governs the daily functioning of the human body and mind. Chronotypes are individual differences in the setting of this biological clock that influence preferences for the optimal timing of daily periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 196 publications
(381 reference statements)
0
4
0
Order By: Relevance
“…Thereby supporting the need for chronotype-based scheduling to reduce the health impact of night shift duties as reported and suggested by various other studies [ 40 ]. Indeed, the idea of circadian scheduling has been suggested to drive more efficient leadership based on better decision-making [ 41 , 42 ], a feature that is needed in the fast-paced ICU environment to drive better patient outcomes. Aside from the health implications of insomnia, fatigue, and depression, various studies have reported reduced quality of care offered and higher error rates among healthcare workers that worked night shifts compared with those who work mainly day shifts [ 13 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby supporting the need for chronotype-based scheduling to reduce the health impact of night shift duties as reported and suggested by various other studies [ 40 ]. Indeed, the idea of circadian scheduling has been suggested to drive more efficient leadership based on better decision-making [ 41 , 42 ], a feature that is needed in the fast-paced ICU environment to drive better patient outcomes. Aside from the health implications of insomnia, fatigue, and depression, various studies have reported reduced quality of care offered and higher error rates among healthcare workers that worked night shifts compared with those who work mainly day shifts [ 13 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of one recent study highlight the significance of leaders' participation (i.e., practising psychological reattachment themselves); on days when leaders psychologically reattached to their work, they experienced more workplace vitality and demonstrated more transformational leadership behaviours (Fritz et al, 2021). Another study shows that supervisors' sleep patterns and sleep behaviour have effects on their own and subordinates' performance and hence how important it is to consider individual needs (Volk et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These results emphasize the need to take a circadian perspective on recovery from work more seriously in future research. While this circadian perspective has been theoretically suggested (Zijlstra et al, 2014) and has already been applied to other fields of organizational behavior (e.g., leadership; Volk et al, 2023), it has rarely found its way into empirical recovery research (Völker et al, 2023). Neglecting this circadian perspective is a crucial oversight because circadian processes determine employees' peaks and troughs as well as upregulation and downregulation of energetic and cognitive resources during the day.…”
Section: Theoretical Implicationsmentioning
confidence: 99%